Redox Sensing within the Genus Shewanella - Harris, Howard W.; Sánchez-Andrea, Irene; McLean, Jeffrey S.; Salas, Everett C.; Tran, William; El-Naggar, Mohamed Y.; Nealson, Kenneth H. (Frontiers in Microbiology, 2018)
A novel bacterial behavior called congregation was recently described in Shewanella oneidensis MR-1 as the accumulation of cells around insoluble electron acceptors (IEA). It is the result of a series of “run-and-reversal” events enabled by modulation of swimming speed and direction. The model proposed that the swimming cells constantly sense their surroundings with specialized outer membrane cytochromes capable of extracellular electron transport (EET). Up to this point, neither the congregation nor attachment behavior have been studied in any other strains. In this study, the wild type of S. oneidensis MR-1 and several deletion mutants as well as eight other Shewanella strains (Shewanella putrefaciens CN32, S. sp. ANA-3, S. sp. W3-18-1, Shewanella amazonensis SB2B, Shewanella loihica PV-4, Shewanella denitrificans OS217, Shewanella baltica OS155, and Shewanella frigidimarina NCIMB400) were screened for the ability to congregate. To monitor congregation and attachment, specialized cell-tracking techniques, as well as a novel cell accumulation after photo-bleaching (CAAP) confocal microscopy technique were utilized in this study. We found a strong correlation between the ability of strain MR-1 to accumulate on mineral surface and the presence of key EET genes such as mtrBC/omcA (SO_1778, SO_1776, and SO_1779) and gene coding for methyl-accepting protein (MCPs) with Ca+ channel chemotaxis receptor (Cache) domain (SO_2240). These EET and taxis genes were previously identified as essential for characteristic run and reversal swimming around IEA surfaces. CN32, ANA-3, and PV-4 congregated around both Fe(OH)3 and MnO2. Two other Shewanella spp. showed preferences for one oxide over the other: preferences that correlated with the metal content of the environments from which the strains were isolated: e.g., W3-18-1, which was isolated from an iron-rich habitat congregated and attached preferentially to Fe(OH)3, while SB2B, which was isolated from a MnO2-rich environment, preferred MnO2.